Characterization of uniquely tumorigenic cancer stem cells in salivary gland adenoid cystic carcinoma - Warner, Kristy A.; Sahara, Sosuke; Herzog, Alexandra E.; Nör, Felipe; Castilho, Rogerio M.; Polverini, Peter J.; Nör, Jacques E. (Frontiers in Oral Health, 2025)
BackgroundCancer stem cells (CSC) are endowed with multipotency, self-renewal and unique tumorigenic potential. They have been identified as cells with high activity of aldehyde dehydrogenase (ALDH) and high expression of CD44 in head and neck squamous cell carcinoma (HNSCC). The objective of this work is to understand whether salivary gland adenoid cystic carcinoma contain CSCs and whether they exhibit a unique tumorigenic activity in this cancer.MethodsWe used flow cytometry, salisphere and western blot assays with 3 human ACC cell lines (UM-HACC-2A, UM-HACC-14, UM-HACC-6) to characterize the impact of ALDH activity and CD44 expression. In vitro results were verified in vivo by orthotopic injection of cells retrieved from a patient-derived xenograft (PDX) model of ACC (UM-PDX-HACC-14) in the submandibular gland of SCID mice. Primary tumor and metastatic spread were evaluated by 2 pathologists blinded for experimental conditions.ResultsThe fraction of ALDHhighCD44high cells in UM-HACC-2A, UM-HACC-14 and UM-HACC-6 ranged from 3% to 8%. ALDHhighCD44high cells formed more salispheres and expressed higher levels of stem cell markers (e.g., Notch2, Bmi-1) compared to control ALDHlowCD44low cells. ALDHhighCD44high cells sorted from the ACC PDX tumors were more tumorigenic upon orthotopic transplantation into submandibular salivary glands and generated more lung metastases than control ACC cells. Strong ALDH1A1 staining was observed in the majority of salivary gland tumors and lung metastases generated by transplantation of ALDHhighCD44high cells.ConclusionsWe conclude that salivary gland adenoid cystic carcinoma contain a small population of uniquely tumorigenic cells characterized by high ALDH activity and expression.